Design and Implementation of Ubiquitous Fraction App for Fraction Learning in Authentic Contexts (Proceedings of the International Conference on Education, 2020)
An amount of research had identified some difficulties that were faced by students when they learned fractions, which known as one of the essential parts of mathematics. On the other hand, designing mathematics learning in authentic contexts could beneficial to students, such as increase their motivation and collaboration. Thus, we develop a Ubiquitous App, namely Ubiquitous Fraction (U-Fraction), to facilitate fraction learning in authentic contexts by providing useful features. This study was designed to investigate the relationship among three categories of learning variables, including quantity of learning, quality of learning, and learning achievement, and to identify sequences of interactions when students use U-Fraction in authentic contexts. There were 27 five-grade students participated in this study. The data were analyzed using parametric and nonparametric tests, including pair t-test, correlation, lag sequential, and descriptive analysis. In summary, four important findings are highlighted in this study. First, the pair t-test result showed that there was a significant difference in students’ acquisition of fraction knowledge before and after the learning process. Second, the importance of correlation analysis results indicated that students’ learning achievement would more depend on their quality of learning rather than their quantity of tasks that had been solved by them. Third, results from sequential analysis indicated that students intended to do the next steps after they finished the previous step in fraction learning with authentic contexts. Fourth, a questionnaire, which is Sustainable and Scalable Authentic Learning (SSAL), results indicated that most students agree that learning with U-Fraction in authentic contexts could have a positive impact on the ability to collaborate with others. Finally, the limitations of this study also discussed.
Keywords: authentic contexts; ubiquitous fraction; authentic learning; peer sharing; peer assessment